Numerical simulation of realistic top coal caving intervals under different top coal thicknesses in longwall top coal caving working face - Chuang Liu (Nature Portfolio, 2021)
Abstract In the process of longwall top coal caving, the selection of the top coal caving interval along the advancing direction of the working face has an important effect on the top coal recovery. To explore a realistic top coal caving interval of the longwall top coal caving working face, longwall top coal caving panel 8202 in the Tongxin Coal Mine is used as an example, and 30 numerical simulation models are established by using Continuum-based Distinct Element Method simulation software to study the top coal recovery with 4.0 m, 8.0 m, 12.0 m, 16.0 m, 20.0 m and 24.0 m top coal thicknesses and 0.8 m, 1.0 m, 1.2 m, 1.6 m and 2.4 m top coal caving intervals. The results show that with an increase in the top coal caving interval, the single top coal caving amount increases. The top coal recovery is the highest with a 0.8 m top coal caving interval when the thickness of the top coal is 4.0 m, and it is the highest with a 1.2 m top coal caving interval when the coal seam thickness is greater than 4.0 m. These results provide a reference for the selection of a realistic top coal caving interval in thick coal seam caving mining.